Reviews (Medieval and Modern Matters, 2014)
Abstract Sebastiaan Ostkamp, 2013: Aen taefele. Eten en leven in de late middeleeuwen; De Collectie Aad Penders (Mealtimes. Dining and manners in the Late Middle Ages; The Aad Penders collection (Roos van Oosten)